Analisis Morfosintaksis dan Semantik dalam Pembelajaran Bahasa Inggris bagi Mahasiswa Hukum, Manajemen, dan Sistem Informasi di Universitas Murni Teguh - Simorangkir, Imelda; Tarigan, Sri Ninta (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
This study aims to analyze the morphosyntactic forms and semantic meanings of English tenses in students’ utterances across three study programs: Law, Management, and Information Systems at Universitas Murni Teguh. Data were collected from 43 respondents through 40 grammar test items covering four tense categories: Present, Past, Present Perfect, and Future. Findings show that students’ understanding of tense structures varied. The highest mastery was found in the Past and Future tenses, while the most common errors appeared in the Present Perfect Tense. Morphologically, students generally understood basic subject–verb agreement but struggled with consistency in auxiliary verb usage and temporal alignment. Semantically, errors were mainly caused by first language interference (Indonesian) and limited exposure to English in academic contexts. This study emphasizes the importance of meaning-based and contextual grammar instruction that integrates both form and meaning, enabling students, particularly from non-language disciplines, to use tenses accurately in academic and professional communication.